Perbandingan Sistem Evaluasi Pendidikan di Indonesia dan Finlandia :Implikasi Terhadap Kualitas Pembelajaran - Siti Badriyah; Irfan Syafei Siregar; Muhammad Dzikrullah; Nurul Izzah Yasmin; Aprizal Ahmad (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study compares the educational evaluation systems in Indonesia and Finland and their implications for learning quality. The method used is a library study, collecting data from literature related to educational evaluation policies in both countries. The educational evaluation system in Indonesia is quite complex, implementing various forms of assessment, such as homework (PR), daily tests, mid-semester assessments (PTS), final semester assessments (PAS), and school exams (US). Indonesia also implements the Minimum Completion Criteria (KKM) as a requirement for student graduation. In contrast, Finland implements a simpler evaluation system with an emphasis on formative evaluation, a reduced number of exams, and the absence of the KKM or National Exam (UN). In the Finnish system, students are not held back from a grade, and evaluation is conducted throughout the learning process, focusing on students' continuous development. The results of this study indicate that differences in evaluation systems have a significant impact on learning methods and the development of educational quality in each country. The implication is the need to adapt evaluation policies that integrate holistic and formative aspects to improve learning quality, particularly in Indonesia.